The Development of General Elections and Regional Head Elections After the Reformasi Era - Andayani Bs, Dwi; Muhammad Rizqi Fadhlillah (Journal of Law, Politic and Humanities, 2023)
Indonesia is a constitutional state (Rechtsstaat) that upholds the values of legal norms based on laws. Indonesia has the highest legal norms, namely Pancasila and the 1945 Constitution of the Republic of Indonesia. Therefore, all forms of legislation that are made must not conflict with the 1945 Constitution of the Republic of Indonesia. in the Indonesian constitutional system experienced a very significant change. The implementation of direct and simultaneous elections in the post-reform era was held on April 17 2019, which is historical in the electoral process in Indonesia. This is an implication of the Constitutional Court Decision Number 14/PUU-XI/2013 concerning the judicial review case of the Law of the Republic of Indonesia Number 42 of 2008 concerning the General Election of President and Vice President. directly by the people. Simultaneous election implementation which will be held in 2024, this has been stipulated in the Law of the Republic of Indonesia Number 7 of 2017 concerning General Elections and the Law of the Republic of Indonesia Number 10 of 2016 concerning the Second Amendment to Law Number 1 of 2015 Concerning the Stipulation of Government Regulation in Lieu of Law Number 1 of 2014 Concerning the Election of Governors, Regents and Mayors to Become Laws. The two laws mandate that in 2024 elections will be held simultaneously in 1 (one) year, namely presidential and vice-presidential elections, legislative elections and regional head elections. In addition, there is a provision regarding the presidential threshold that has existed since the 2004 election.